The Role of Passing Clouds Home Industry to Support The Tourism Activity in The Musk Victoria Australia - Roels, Ni Made Sri Puspa Dewi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Passing Clouds is a home industry that produces wine and offers tourism activities which are one of the leading choices when visiting Musk City, Victoria. This research aims to provide an overview of what tourist activities can be done by tourists when visiting Passing Clouds. The research approach used is exploratory research. Observation, interviews, and documentation do methods of data collection. Interviews were conducted using an in-depth interview model with informants using purposive sampling. The key informant is the owner of Passing Clouds himself; the total number of informants is ten people. The data analysis method used is the qualitative data analysis method in the field of the Spradley Model. The results of this study describe the tourist activities that tourists can do when visiting Passing Clouds, namely The Winery, Dining Room, Cellar Doors, and The Caravino. Wineries in the form of tourists can see the wine-making process starting from the cultivation of grapes, storage of stock materials, and wine production to the wine distribution process. The dining room is in the form of Fine Dining with views of the vast vineyard accompanied by wine produced directly from Passing Clouds, Cellar Door tourists can try a variety of wine products, and The Caravino in the form of picnic boxes provided every summer and spring.